Tingkat Kontaminasi dan Potensi Risiko Ekologis Logam Berat Besi (Fe) dan Merkuri (Hg) pada Sedimen di Perairan Selangan Kota Bontang Kalimnatan Timur - Wa Ode Siti Safiyah; Sarndika Sarndika; Fitriyana Fitriyana (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2026)
This study aims to evaluate the level of heavy metal pollution and the potential ecological and human health risks in the waters of Selangan, Bontang City. The research focuses on analyzing the concentrations of iron (Fe) and mercury (Hg) in sediment, considering that both elements are toxic, persistent, and capable of bioaccumulating within the food chain. The study was conducted over six months, from January to June 2023, at four sampling stations representing the environmental conditions of Selangan waters. The methodology included sediment sampling, sample preparation through drying and grinding, and laboratory analysis using Inductively Coupled Plasma–Optical Emission Spectrometry (ICP-OES) to determine Fe concentrations. The results were then compared with quality standards established by the Washington Annotated Code 173-204-320 and Indonesia’s National Agency of Drug and Food Control (BPOM) Regulation No. 5 of 2018. The findings indicate the presence of heavy metal contamination across all sampling stations. Fe concentrations ranged from 2.35 mg to 6.308 mg, significantly exceeding the permissible limit of 0.3 mg/L. Meanwhile, Hg concentrations ranged from 0.015 mg to 0.028 mg, also surpassing the standard threshold of 0.001 mg/L. These results clearly demonstrate heavy metal pollution in the Selangan waters, posing potential threats to marine ecosystem health and coastal communities. Regular monitoring and mitigation measures are urgently recommended to prevent further environmental degradation.